2022
DOI: 10.15587/1729-4061.2022.259791
|View full text |Cite
|
Sign up to set email alerts
|

Determining the rational parameters for processing spent etching solutions by ferritization using alternating magnetic fields

Abstract: This paper reports the results of studying the application of a ferritization method for the integrated purification of used etching solutions. A feature of this work is the use of energy-saving activation of the process by alternating magnetic fields. Its advantages are shown in comparison with traditional thermal activation. The influence of magnetic induction amplitude and key technological parameters of ferritization on the quality of cleaning an etching solution has been studied. The qualitative and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These compounds of a crystalline structure quickly sediment during processing, their volume and humidity are much lower than those of iron hydroxides [9]. A fairly common method of such processing of spent etching solutions is the method of ferritization using variable magnetic fields [12]. At the same time, the energy efficiency of STS processing process increases, magnetite deposits are formed, which are easily disposed of.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…These compounds of a crystalline structure quickly sediment during processing, their volume and humidity are much lower than those of iron hydroxides [9]. A fairly common method of such processing of spent etching solutions is the method of ferritization using variable magnetic fields [12]. At the same time, the energy efficiency of STS processing process increases, magnetite deposits are formed, which are easily disposed of.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The ferritization process promotes the rapid formation of dispersed substances with magnetic properties. The disadvantages of traditional ferritization are its temperature requirements-temperatures above 75 • C. In research paper [27], it was shown that an alternative to thermal ferritization is the activation of the reaction mixture with alternating magnetic fields (AMF) at ambient temperatures. Using this activation method, in research paper [28], iron-containing ferromagnetic compounds of various phase compositions were obtained from liquid industrial waste, the structure of which contains nickel, zinc, and copper ions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during the chemical purification of washing water from galvanic production from heavy metals using alkaline precipitators, it was found that when Fe 3 + and/ or Al 3 + cations are present in wastewater or salts of these metals are used as coagulants, the residual content of heavy metal cations is significantly lower than those calculated from the solubility of the corresponding hydroxides. The process of formation of a precipitate with reduced solubility in the presence of Fe-ions was called "ferritization" [10][11][12] because heavy metal ferrites were found in the sediment. However, an analysis of published data shows that ferrites are characteristic of metals that easily form oxides in an aqueous medium (Zn, Cu).…”
Section: Introductionmentioning
confidence: 99%